If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2p + 7 + 3p = 12 Reorder the terms: 7 + -2p + 3p = 12 Combine like terms: -2p + 3p = 1p 7 + 1p = 12 Solving 7 + 1p = 12 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 1p = 12 + -7 Combine like terms: 7 + -7 = 0 0 + 1p = 12 + -7 1p = 12 + -7 Combine like terms: 12 + -7 = 5 1p = 5 Divide each side by '1'. p = 5 Simplifying p = 5
| 10(x+5)+68=-16-16 | | 6-5(ln)x=8 | | 14-h=0 | | ((b^3)/(-2a^2))^3 | | 2.3x-18=0 | | 4a+2b+3a-b= | | H=-16t^2-11t+200 | | 11x-2=7x+11 | | 5x^2-24x+33=0 | | 2x^2+y^2-6x=0 | | 4x-9=51 | | 5x=8x+13 | | 2p=5p | | 3+10x=3+x | | 160=-16t^2+112t | | 10x-12=180 | | 72+6x=22-14x | | 30/50= | | 59+x=180 | | 18x+21=3x^2 | | 4(r+2)=-16 | | w(w^2-3)=14 | | ((x*10)+(y*40))*52=42000 | | (x*10+y*40)*52=42000 | | 6n=5+n | | (3x^7)(7x^3)/(x^21) | | -92=5x+8 | | I-4(5+7y)+6(2y-9)= | | 10x+4=15x+5 | | 10x+9=129 | | 10x-2=8(x+2) | | 9x=xsquare+23x-42 |